COMPETENCES AND OUTCOMES OF LEARNING: THE LOGIC OF THEIR REPRESENTATION IN EDUCATIONAL PROGRAMMES - Elena G. Yelina; Elena N. Kovtun; Svetlana E. Rodionova (Высшее образование в России)
The article covers the experience the Presiding members of the Philology scholarly methodological council of the training and methodology union of classical universities have got in representing the results of learning in the process of professional competences formation associated with the elaboration of a Bachelor of Philology approximate curriculum. The article brings up the issues that got their shape in the process of this work and it also puts forward some suggestions on possible algorithms of the formulation of educational outcomes and the criteria of their assessment which could fit all the levels of Philological training, on the basis of methodological findings of the TUNING international project (“Tuning educational structures in Europe”).